Edukasi Pemanfaatan Tanaman Serai sebagai Tanaman Herbal Rumah Tangga untuk Anti Inflamasi di Posyandu Pucuk Rebung Kuntum Bersusun - Yessi Rahayu; Evy Eryta; Sabrina Hayati; Goldha Faroliu Peadutu; Putri Wulandini; Attachira Br. Ritonga; Cheesa Prisilla Ronald; Oriza Sativa; Muhammad Arief Mustaqim; Egis Feby Asyaroh (Jurnal Nusantara Berbakti, 2025)
Lemongrass (Cymbopogon citratus) is a traditional medicinal plant with high anti-inflammatory potential. Its chemical components, such as citral, citronellal, and flavonoids, are effective in reducing inflammation, pain, and tissue damage. These benefits are highly significant in treating conditions such as arthritis, asthma, and various other inflammatory diseases. As a natural alternative treatment, lemongrass offers safety and efficacy without harmful side effects. The use of lemongrass can enhance the quality of life and community health while reducing dependence on chemical medications. Therefore, lemongrass deserves consideration as an effective and natural anti-inflammatory treatment option.The objective of this activity is to educate the community on the utilization of lemongrass as a household herbal drink with anti-inflammatory properties. In this program, the community service team will provide education and guidance to the community on how to process lemongrass (herbal medicine) into a household herbal drink with anti-inflammatory benefits.This activity will take place in one of the neighborhoods in Pekanbaru City, specifically at the Pucuk Rebung Kuntum Bersusun Posyandu, located at Jl. Limbungan, Komplek BPD No. 56, Rumbai Timur District, Lembah Sari Subdistrict, Pekanbaru City, Riau Province.The goal of this program is to increase the knowledge of the women at Pucuk Rebung Kuntum Bersusun Posyandu, enabling them to maximize the use of lemongrass (herbal medicine) for their health and well-being.